PHYTOCHEMICAL SCREENING OF SELECTED SPECIES FROM CONVOLVULACEAE - Mascarenhas, Maria Emilia; Mandrekar, Cibani Ramesh; Marathe, Pratiksha Bharat; Morais, Luena Joey (International Journal of Current Pharmaceutical Research, 2017)
Objective: To screen phytochemicals from stems and leaves of 23 selected taxa of Convolvulaceae. Methods: Stem and leaves of the selected 23 taxa were collected and shade dried. Methanol extract was used for preliminary screening of phytochemicals such as alkaloids, carbohydrates, glycosides, saponins, proteins, phytosterols, tepenoids, fixed oils, phenolic compounds, flavonoids and tannins. Results: Phytochemicals were present in all selected taxa of Convolvulaceae. Leaves showed most of the phytochemicals than stems. The important phytochemicals in leaves were flavonoids, carbohydrates, alkaloids, saponins, tannins and phenolic compounds while those in stems were carbohydrates, saponins and phenolic compounds. Proteins and fixed oils were absent in the taxa studied. Conclusion: Phytochemical screening in the present study, revealed that maximum phytochemicals were present in leaves than in stems.